Evidence that cytochrome b559 is involved in superoxide production in photosystem II: effect of synthetic short-chain plastoquinones in a cytochrome b559 tobacco mutant - Pospísil, Pavel; Snyrychová, Iva; Kruk, Jerzy; Strzałka, Kazimierz; Naus, Jan (The Biochemical journal, 2006)
Light-induced production of superoxide (O2*-) in spinach PSII (photosystem II) membrane particles was studied using EPR spin-trapping spectroscopy. The presence of exogenous PQs (plastoquinones) with a different side-chain length (PQ-n, n isoprenoid units in the side-chain) enhanced O2*- production in the following order: PQ-1>PQ-2>>PQ-9. In PSII membrane particles isolated from the tobacco cyt (cytochrome) b559 mutant which carries a single-point mutation in the beta-subunit and also has a decreased amount of the alpha-subunit, the effect of PQ-1 was less than in the wild-type. The increase in LP (low-potential) cyt b559 content, induced by the incubation of spinach PSII membrane particles at low pH, resulted in a significant increase in O2*- formation in the presence of PQ-1, whereas it had little effect on O2*- production in the absence of PQ-1. The enhancement of O2*- formation induced by PQ-1 was not abolished by DCMU [3-(3,4-dichlorophenyl)-1,1-dimethylurea]. Under anaerobic conditions, dark oxidation of LP cyt b559 increased, as pH was decreased. The presence of molecular oxygen significantly enhanced dark oxidation of LP cyt b559. Based on these findings it is suggested that short-chain PQs stimulate O2*- production via a mechanism that involves electron transfer from Pheo- (pheophytin) to LP cyt b559 and subsequent auto-oxidation of LP cyt b559.
Keywords: mutace; cytochromy typu b; Diuron; Superoxides; Hydrogen-Ion Concentration; Spectrophotometry; diuron; Time Factors; časové faktory; Plastoquinone; Nicotiana; Photosystem II Protein Complex; Mutation; superoxidy; Spinacia oleracea; fotosystém II (proteinový komplex); oxidace-redukce; Point Mutation; spektrofotometrie; Oxidation-Reduction; Oxygen; bodová mutace; plastochinon; tabák; koncentrace vodíkových iontů; kyslík; Cytochrome b Group